Optimizing Poultry Growth and Meat Quality: Effects of Guanidinoacetic Acid Supplementation in Yellow-Feathered Broilers - Jian Xiao; Lifen Wang; Yuguang Chen; Kai Xiao (Veterinary Sciences)
This study investigated the effects of dietary guanidinoacetic acid (GAA) supplementation on growth performance, carcass traits, meat quality, intestinal morphology, and cecal microbiota composition in yellow-feathered broilers. A total of 360 one-day-old chicks were randomly assigned to five groups with diets containing 0 (control), 300 mg/kg, 600 mg/kg, 900 mg/kg, and 1200 mg/kg GAA. In the initial growth phase, GAA supplementation increased average daily gain (ADG) by 13.01%, 8.97%, and 12.95% for the 300, 600, and 900 mg/kg groups, respectively, and reduced the feed conversion ratio (FCR), though these changes were not statistically significant (p > 0.05). Higher GAA dosages (900 and 1200 mg/kg) improved post-slaughter pH levels in breast muscle, indicating better meat quality, and significantly enhanced intestinal barrier function by increasing villus height and the villus-to-crypt ratio. However, 1200 mg/kg GAA led to a significant increase in serum ALT levels, raising concerns about potential liver stress. Overall, 900 mg/kg GAA supplementation demonstrated the most beneficial effects across various parameters, suggesting it as an optimal dosage to enhance production performance and meat quality in yellow-feathered broilers. Future studies are encouraged to investigate its long-term safety and underlying mechanisms.